2009
DOI: 10.1177/0306624x09337390
|View full text |Cite
|
Sign up to set email alerts
|

Profiling Property Criminals in Turkey

Abstract: The main aim of this research is to develop a profile of a thief. Through a comprehensive survey of property crime suspects arrested in the city of Ankara between 2004 and 2005, the authors have attempted to determine the socioeconomic qualities of those involved in these forms of property crimes. Results of the study show that property crimes are a consequence of low education, lack of occupational skills, and alcohol and drug addiction on the part of the offenders. Because of these factors, theft becomes a w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
3
0
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 20 publications
1
3
0
1
Order By: Relevance
“…Overall, the low rate of mental well-being was compatible with other similar studies (1)(2)(3)(4)(5)20). According to the results of some other studies, about 50% of the USA population had comorbid mental disorder and drug abuse (21,22). Furthermore, about 30 -50% of psychiatric patients in clinical centers were also drug abusers (23).…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…Overall, the low rate of mental well-being was compatible with other similar studies (1)(2)(3)(4)(5)20). According to the results of some other studies, about 50% of the USA population had comorbid mental disorder and drug abuse (21,22). Furthermore, about 30 -50% of psychiatric patients in clinical centers were also drug abusers (23).…”
Section: Discussionsupporting
confidence: 88%
“…In this study, in the presence of confounding variables drug abusers with the lowest level of education had higher chances of committing crimes than drug abusers with higher levels of education. According to the study by Icli et al (22) low education, and lack of occupational skills, and drug abuse have a direct correlation with criminal activity (22). It seems that high educational level has been associated with the high of awareness of the obscenity crime consistently.…”
Section: Discussionmentioning
confidence: 98%
“…1 Η βιαιοπραγία φαίνεται να είναι πιθανότερη στις χαμηλότερες κοινωνικοοικονομικές τάξεις, σε ανέργους, σε άστεγους και σε άτομα με χαμηλότερη εκπαίδευση. [2][3][4] Ένα άτομο έχει αυξημένες πιθανότητες επιθετικό τητας εάν έχει ιστορικό συλλήψεων για βίαιη συμπε ριφορά, ιστορικό ψυχιατρικής νοσηλείας πριν από την ηλικία των 18 ετών καθώς και αν υπάρχει ιστορι κό εμπρησμών και κακοποίησης ζώων. 1 H χρήση κάνναβης και ναρκωτικών συνδέεται με την εκδήλωση ένοπλης βίας, παρορμητικώναπερί σκεπτων πράξεων και βίαιων εγκλημάτων.…”
Section: εισαγωγήunclassified
“…In line with this, some studies have also found that migration increases the level of property crime (8,30) and has no effect on violent crime (8). A study in Denmark suggested that property-related crimes may be associated with common criminal factors (12), such as low education and a lack of occupational skills (31). It has also been suggested that the differences in labor market opportunities for different migrant groups could shape the potential impact on crime (8).…”
Section: Discussionmentioning
confidence: 89%